O projeto horizonte 2020 na rede jesuíta de educação: construindo caminhos para inovação na Educação Infantil do Colégio Anchieta, Nova Friburgo/RJ - Alves, Gisele Martins (Universidade do Vale do Rio dos Sinos, 2018)
This recent research had the goal of gathering ideas with Colegio Anchieta´s educative community, from Nova Friburgo, Rio de Janeiro, adding towards participative management in the process of innovation of the pedagogic project in Children´s Education. Once getting to know the deep changes in education that are going on in Horizon 2020 project, in Spain, it has been a reference to understand and to learn how we can, together, transform an educational project. The bibliographical research done has identified six areas of work in the process of innovation that have been references in the process of listening to the ideas of the education community about their innovational priorities regarding methods, contents and values, educational facilities, students and teachers, technologies and resources, and family and surroundings. The presentation of the proposal of research and the delivery of a letter of invitation during a meeting with parents was the starting point for the participation of the children´s education community, which was operationalized by a questionary, answered by adhesion. The field research was answered by 68 people out of a total of 193 possible participants. The data analysis has also involved the discursive textual analyzsis (DTA) of the presented ideas in the open question: “Which suggestion would you like to present in order to help us building ways of innovation in the Children´s Education of Colegio Anchieta? Give us your best thoughts!”. Analysing the data received, we have developed the ideas for the construction of innovative routes in Children´s Education of Colegio Anchieta, Nova Friburgo. We have come to the conclusion that they have some crystal clear innovation proposals in some of the areas of work and there are some other that demand us to keep our ears open to the community. For this, in the return of the research, we developed an Pedagogical Letter of the research to the community where we have exposed the main ideas of innovation and also the main questions that suggest the continuous need of exchanging ideas. The research has helped us to realize what are the points that need to be changed and also the understanding about the importance of development of a of participative culture in the school and the need of having more channels of community participation.

La presente pesquisa tuvo como objetivo realizar la captación de ideas con la comunidad educativa del Colegio Anchieta de Nova Friburgo, Rio de Janeiro, contribuyendo para la gestión participativa en el proceso de innovación del proyecto pedagógico de la Educación Infantil. El conocimiento del cambio profundo de la educación que está sucediendo en el Proyecto Horizonte 2020, en España, fue una referencia para comprender como juntos podemos transformar un proyecto educativo. El estudio bibliográfico del referido proyecto indicó seis ámbitos de trabajo en el proceso de innovación en el contexto de las escuelas jesuitas en España, que sirvieron de referencia para realizar, en esta investigación, la escucha de la comunidad en cuanto a sus prioridades de innovación en relación a: métodos, contenidos y valores; espacios educativos; alumnos y maestros; tiempo y organización; tecnologías y recursos; familia y entorno. La presentación de la propuesta de investigación a la comunidad y la entrega de una Carta Invitación en una reunión de padres fue el punto de partida para la participación de la comunidad de la educación infantil, que se dio por medio de un cuestionario, respondido por adhesión. La investigación de campo contó con 68 participantes, de un total de 193 invitados. En cuanto el análisis de los resultados, además de los datos cuantitativos, se utilizó el procedimiento del Análisis Textual Discursiva (ATD) de las ideas presentadas en la cuestión, abierta: "¿Le gustaría ofrecer una buena idea para que construyamos caminos de innovación en la Educación Infantil del Colegio Anchieta? ¡Haga su sugerencia!". Del análisis de los datos resultó el levantamiento de ideas para la construcción de caminos de innovación en la Educación Infantil del Colegio Anchieta, Nova Friburgo. Se concluyó que ya existen claras proposiciones de innovación en algunos ámbitos de trabajo, mientras otros merecen la continuidad de la escucha de la comunidad. Por eso, para la devolución a la comunidad, se elaboró una Carta Pedagógica Devolutiva de la Pesquisa comunicando las principales ideas de innovación, así como los principales cuestionamientos que sugieren la continuidad del diálogo. De esta forma, la pesquisa contribuyó para la reflexión sobre lo que debemos alterar, bien como para la comprensión sobre la importancia de la creación de una cultura participativa en la escuela y de la necesidad de ampliación de los canales de participación de la comunidad en la escuela.
Keywords: Projeto Horizonte 2020; Educação Infantil; Gestão participativa; Inovação; Horizon 2020 Project; Infantile Education; Participative management; Innovation; Proyecto Horizonte 2020; Educación Infantil; Gestión participativa; Innovación; ACCNPQ::Ciências Humanas::Educação